Perspectives of Regionalisation in Europe - Gołda-Sobczak, Maria (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2015)
The notion of region is particularly vague, as this issue is referred to by studies from various disciplines. It has long been one of the subjects of interest of the Council of Europe which perceives local and regional administration as one of the fundamental ingredients of modern European democracy. The European Charter of Local Self-Government is the main document that regulates these matters in the Council of Europe law system. It is accompanied by a number of other documents, including The European Charter of Regional Self-Government. The article provides an analysis of these normative deeds within the realm of Union law. When the Single European Act entered into force, regions have become an important part of Union policy. Committee of the Regions set up in 1994, whose operation is related to the principle of subsidiarity and programming of the idea of the Europe of Regions, is the most important body concerned with regional issues.

Pojęcie regionów jest wyjątkowo nieostre, gdyż problematyki tej dotyczą prace z różnych dziedzin. Kwestia ta od dawna stanowiła jeden z przedmiotów zainteresowania Rady Europy, która w lokalnej i regionalnej administracji widzi jeden z podstawowych składników nowoczesnej demokracji europejskiej. Podstawowym dokumentem regulującym te sprawy w systemie prawa Rady Europy jest Europejska Karta Samorządu Lokalnego. Towarzyszy jej szereg innych dokumentów, w tym Europejska Karta Samorządu Regionalnego. W treści artykułu dokonano analizy wspomnianych aktów normatywnych w obszarze prawa unijnego regiony stały się ważną częścią polityki Unii po wejściu w życie Jednolitego Aktu Europejskiego. Najważniejszym z organów zajmujących się problematyką regionalną jest Komitet Regionów ustanowiony w 1994 r., którego funkcjonowanie związane jest z zasadąpomocniczości i programowaniem idei Europy Regionów.
Perspektywy regionalizacji w Europie
Keywords: Regionalisation; region; regional co-operation; European Charter of Local Self-Government; European Charter of Regional Self-Government; Council of Europe; European Union; Regionalizacja; region; współpraca regionalna; Europejska Karta Samorządu Lokalnego; Europejska Karta Samorządu Regionalnego; Rada Europy; Unia Europejska